Penegakan Peraturan, Moralitas Individu, Kesesuaian Kompensasi, Komitmen Organisasi, dan Kecenderungan Kecurangan - Putri, Valda Jeanitta Dwi; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
The research objective was to examine the effect of enforcement, individual morality, appropriateness of compensation, and organizational commitment on fraud tendencies. The research was conducted at Denpasar City Government Offices, totaling 20 offices with a total sample of 137 employees. Purposive sampling technique is used as a technique in sampling using a questionnaire. Research findings, namely enforcement of regulations have a negative effect on the tendency to cheat, while individual morality, appropriateness of compensation, and organizational commitment have no effect on the tendency to cheat. The research provides an overview and information to the Denpasar city government which can be input in an effort to prevent acts of fraud. Keywords: Rule Enforcement; Individual Morality; Compensation Suitability; Organizational Commitment; Fraud Tendencies